MIRCEA ELIADE AND ALEJO CARPENTIER IN LIGHT OF R.G. ECHEVARRÍA'S ONTOLOGICAL/ EPISTEMOLOGICAL BINARY IN MAGICAL REALISM - Maria-Ana Tupan (Incursiuni în imaginar)
Associated with German post-expressionism, new objectivity, French surrealism and dadaism, magic realism is regarded as an ontological scandal, a violation of the logic of identity through the invention of a third level of reality. The name was coined by a German critic and art historian, Franz Roh, in his book “Nach-Expressionismus. Magischer Realismus. Probleme der neuesten europäischen Malerei”, published in 1925, and employed again in Foto-Auge, a book on the new phtography jointly published by Roph with Jan Tschichold which served as a catalogue for the avant-garde “Film und Foto” exhibition (FiFo) held in Stuttgart between May and June 1929. By then, however, Roh’s essay had already been translated into Italian and Spanish and promoted by prominent thinkers of the day, such as Jose Ortega y Gasset, who published it in the influential “Revista de Occidente” in Madrid in 1927, and by Massimo Bonterupelli, who translated it for the Italian journal, “900” ['Novecento']. The prompt and resonant international echo generated by Roh’s new art can hardly be understood otherwise than on the assumption that it was striking a familiar ring in the rapidly changing and polyphonous score of European modernism. Reputed for its international and heterogeneous character, modernism is thus revealed to have been crossed by some common currents of poetic matter and energy. The present essay sets out to dig up the roots of a hybrid, literary and plastic artistic mode in the earlier half of the last century, and to identify legacies in the aftermath of Roh’s celebrated manifesto.